Answer:
option d
Step-by-step explanation:
[tex]\sf \boxed{a^m*a^n = a^{m+n}\\\\}[/tex]
[tex]\sf \left(\frac{m^{-1}m^{5}}{m^{-2}} \right)^{-3} =\left(\dfrac{m^{-1+5}}{m^{-2}}\right)^{-3}[/tex]
[tex]\sf = \left(\dfrac{m^4}{m^{-2}}\right)^{-3}\\\\[/tex]
[tex]\boxed{\dfrac{a^{m}}{a^{n}}=a^{m+n}}[/tex]
[tex]\sf = \left(m^{4-[-2]}\right)^{-3}\\\\ =\left(m^{4+2}\right)^{-3}\\\\ = \left(m^6\right)^{-3}\\\\[/tex]
[tex]\boxed{(a^{m})^n=a^{m*n}}[/tex]
[tex]\sf= m^{6*(-3)}\\\\ = m^{-18}[/tex]
[tex]\boxed{a^{-m}=\dfrac{1}{a^m}}[/tex]
[tex]\sf=\dfrac{1}{m^{18}}[/tex]